Managing Digital Economic Corridors: International Cooperation and Regional Integration in the Digital Age - Jundullah Rifqi Prasmanto; Anang Ma’ruf; Muhammad Fathurrahman Assidiq; Muhammad Faiz Diyaulhaq (TechComp Innovations: Journal of Computer Science and Technology, 2025)
This study explores the complexities of managing Digital Economic Corridors (DECs) within the framework of international cooperation and regional integration. It highlights the necessity of multi-level governance structures that coordinate national, regional, and international stakeholders to ensure effective corridor management. The research identifies critical challenges including policy misalignment, regulatory fragmentation, digital sovereignty conflicts, and significant capacity gaps in developing countries. Public–Private Partnerships (PPPs) are underscored as key drivers of infrastructure development, but require robust oversight to ensure inclusivity and accountability. The study emphasizes that digital sovereignty issues complicate multilateral cooperation by creating competing regulatory regimes and geopolitical tensions. Moreover, capacity limitations in developing nations impede equitable participation in DECs, necessitating sustained international support in digital literacy, policy development, and institutional strengthening. Ultimately, the findings suggest that balanced governance, harmonized regulations, and inclusive capacity-building are essential to unlocking the full potential of DECs as instruments for regional economic growth and digital integration.